Evaluasi Penggunaan Antihipertensi dan Faktor Risiko Pada Ibu Hamil Preeklampsia di Rumah Sakit Fatmawati Jakarta Selatan Tahun 2021 - Ramadhani, Gabriela (RSUP Fatmawati, 2023)
Preeclampsia is defined as hypertension accompanied by proteinuria, occurring after 20 weeks gestation and requiring appropriate antihypertensive therapy. This study aims to determine the use of antihypertensive drugs in preeclampsia patients and to determine the relationship between preeclampsia and patient characteristics (age, gestational age and disease history). The sample research method is total sampling and analyzed descriptively with observational and cross-sectional study designs. The results of the study were 71 patients who received antihypertensive therapy. Nifedipine (29.6%) and metidopa (12.8%) were the most widely used drug choices. The results of drug use efficacy, drug efficacy (92.9%), dose consistency (100%), frequency consistency (100%), suitability of therapy duration (100%) based on clinical practice guidelines for KSM Obsetetri and Gynecology Fatmawati Hospital. Age, gestational age, hypertension comorbidities and diabetes mellitus are demographic profiles related to therapeutic outcomes (p < 0.05). The conclusion of giving antihypertensives to preeclampsia pregnant women is in accordance with the guidelines for clinical practice of KSM Gynecology Fatmawati Hospital and maternal age, gestational age, hypertension comorbidities and diabetes mellitus have a significant relationship with the incidence of preeclampsia while comorbidities of obesity, asthma, and kidney disease are not associated with the incidence of preeclampsia. Keywords: Pregnant women; Preeclampsia; Antihypertensive